Ehrlichia canis and Hepatozoon spp. in captive tigers in Thailand - C. Mongkolphan; A. Saechin; T. Chamsai; P. Sedwisai; R. Boonyarittichaikij; S. Tangsudjai (International Journal for Parasitology: Parasites and Wildlife)
Captive wildlife can serve as reservoirs for various tick-borne pathogens for both domestic animals and humans. Ecotourism tiger parks, where tigers (Panthera tigris) engage with humans and other animals, increase the risk of disease transmission. This study aimed to investigate the infection rate, co-infection patterns, and associated risk factors of tick-borne pathogens (Ehrlichia, Hepatozoon, and Babesia) in captive tigers in Thailand. Blood samples were collected from 100 tigers and analyzed using multiplex PCR to detect the presence of three genera of tick-borne pathogens. The overall infection rate at least one tick-borne pathogen was 17 % (17/100). Ehrlichia canis was the most common, affecting 15 % (15/100) of the tigers, followed by Hepatozoon spp. [5 % (5/100)], with no detected Babesia spp. infection. Ehrlichia canis and Hepatozoon spp. co-infections were confirmed in 3 % (3/100) of the cases. Infection rates were examined according to sex and age. Female tigers exhibited a higher infection rate (22.22 % (10/45)) than males (12.73 % (7/55)), though this difference was not statistically significant (p = 0.209). Age was a significant factor, with older tigers showing higher infection rates (p < 0.001). Co-infections were observed in tigers older than seven years. All infected tigers, single or co-infected, commonly exhibited hyperproteinemia, anemia, and elevated creatinine levels in their blood. All pathogens identified in this study posed health risks to captive tigers, with infection rates primarily influenced by age. Ehrlichia canis poses the highest health risk for captive tigers in Thailand. These findings underscore the importance of routine health monitoring and effective tick control strategies to protect these endangered animals.